CONCEPTUAL DESIGN FOR ADDITIVE MANUFACTURING: AN EXPLORATIVE STUDY. (May 2020) - Valjak, F.; Bojčetić, N.; Nordin, A.; Godec, D.
Abstract: With the broader industrial application of Additive Manufacturing (AM), designers are facing new challenges in conceptual design for AM. To better understand the problematic, the authors organised a design workshop with six experts in AM. The paper presents the results of the conducted design workshop and discusses the current and future trends in research on the conceptual design for AM.